The Influence of Morality and Integrity on Corporate Performance with Anti-Fraud Awareness as an Intervening Variable at PT XYZ - Ali, Mariyuana Abdussamad; Dayona, Gurawan; Sofiati, Nunung Ayu (Journal Integration of Management Studies, 2025)
The phenomenon of fraud within Indonesian state-owned enterprises (SOEs) is becoming increasingly complex and has far-reaching impacts on both company performance and reputation; PT XYZ, as a strategic entity responsible for managing national infrastructure, is highly vulnerable to fraud, which can lead to financial losses and a decline in public trust. With anti-fraud awareness serving as an intervening factor, this study aims to investigate how morality and integrity affect business performance. Academic study employs is quantitative explanatory design using validated questionnaires. Data were collected from 160 employees of PT XYZ’s subsidiary. Analysis was conducted using SmartPLS 3. The study emphasizes the development of an integrative model that simultaneously incorporates the dimensions of morality, integrity, and anti-fraud awareness into a framework of influence on company performance. This model is the first to be tested empirically of its kind., particularly within the context of Indonesia’s infrastructure sector, contributing both theoretical and practical insights into value-based anti-fraud studies in public listed companies. The model introduces a conceptual approach that positions anti-fraud awareness as a mediating element between moral values and integrity, and organizational performance—an area that has been scarcely explored quantitatively in the governance of strategic public enterprises. The findings reveal that morality and integrity have a strong influence on corporate performance. This demonstrates that individual character quality contributes significantly to achieving cleaner and more accountable organizational outcomes. The practical implications of this research support the importance of transforming work culture through value-based human resource development strategies, such as the establishment of a Global Integrity Mentorship Program, implementation of Ethics Nudging, and enhancement of the Psychological Safety Index to foster collective awareness of fraud risk.